A Tövisek és virágok kötetkompozíciója és szöveghálója - Debreczeni, Attila (Studia Litteraria, 2020)
Ferenc Kazinczy’s epigram volume titled Tövisek és virágok (Thorns and Flowers) was canonised as the opening event of the debates surrounding the language reform. This paper attempts to discover the original context of the volume by analysing the cycle composition and the comments and textuality surrounding the poems. First, it reviews the circumstances of the birth and publication of the volume, it discovers the defining factors in the canonisation. Then it reviews the compositional principles of the poem cycle, then the understanding of the reference system and the textual connections of the epigrams follows. The volume (1811) is rooted in the debates of the previous decades, based upon these Pöbel, as the main opponent can be identified with that Calvinist cultural background that Kazinczy mostly criticised and which is named as Debreczen.